รูปแบบการดำเนินชีวิต การแสวงหาข้อมูลและพฤติกรรมการซื้อสินค้าแฟชั่นของผู้หญิงวัยทำงาน - สุพิชา บ้านชี (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
The purposes of this research were 1) to segment working women based on their lifestyles, 2) to study their information seeking behavior of fashion-related products, 3) to study their purchasing behavior of fashion-related products, and 4) to determine the relationship among lifestyles, information seeking and purchasing behavior. Questionnaires were used to collect survey data from 422 working women aged 20-49 years old living in Bangkok. The results were as follows: 1. Lifestyles of working women were segmented into 7 groups; 1) Family and society-oriented group, 2) Achievement oriented group, 3) Fashion conscious group, 4) Conservative group, 5) Self-believed group, 6) Nationalism and Independent group and 7) Sports-challenge lover group. 2. The lifestyles of Family and society-oriented group, Achievement oriented group, Fashion conscious group, Nationalism and Independent group, and Sports-challenge lover group had positive correlations with information seeking behavior. 3. The lifestyles of Family and society-oriented group, Achievement oriented group, Fashion conscious group, Self-believed group, Nationalism and Independent group and Sports-challenge lover group had positive correlations with purchasing behavior. 4. Purchasing behavior had positive correlation with information seeking and lifestyles of working women. เท addition, the analysis of information seeking behavior, psychographic, and demographic variables all together could explain purchasing behavior better than the analysis of information seeking behavior and psychographic variables.